THE ROLE OF LOGICAL PROBLEMS IN IDENTIFYING AND DEVELOPING THE FUNCTIONAL ACTIVITY OF THE RIGHT AND LEFT-BRAIN HEMISPHERES WITHIN THE FRAMEWORK OF ELECTRONIC EDUCATION - Isakova Markhabo Zinnatulloyevna (Modern American Journals, 2025)
The purpose of this research is to study the pedagogical and psychological importance of logical problem-solving in identifying and developing the functional activity of the right and left brain hemispheres within the framework of electronic education.The study was carried out through the LogicMath module, developed by the author, which integrates mathematical logic and creative problem-solving elements to assess hemispheric balance among students.An experimental study involving 120 students at the Tashkent “Temurbeklar maktabi” Military Academic Lyceum revealed that electronic learning environments enhance not only logical-analytical but also visual-creative thinking. This integration of neuroscience principles with digital pedagogy demonstrates that balanced hemispheric activity can significantly improve cognitive flexibility, motivation, and academic performance.
Keywords: Logical thinking, hemispheric activity, electronic education, LogicMath, cognitive development, pedagogy, neuroscience, creativity.